Effect of Herbal Formulation AV/DAC-16 Supplementation on Rumen Profiles in Buffalo Calves (Bubalus bubalis) - Singh, Digvijay; Bhatia, H. (Journal of Buffalo Science, 2012)
12 healthy buffalo calves with BW range 100-150 kg were fistulated and divided into two groups of 6 animals each. Control group animals were fed on conventional diet comprising of wheat straw (2 kg), green fodder (8 kg), concentrate (1.0 kg) and mineral mixture (0.050kg). The animals of the treatment group were kept on diet similar to the control group along with feeding of herbally formulated drug AV/DAC-16@ 15 gm/day for 21 days. Each animal was sampled for three consecutive days at 0 hr i.e., immediately before feeding and subsequent samples were taken at 2, 4 and 6 h intervals after feeding. There was a significant fall in pH at 2 and 4 h post-prandial and in MBRT during the entire observation period. TVFA concentration increased significantly in the treatment group. Though oral administration of AV/DAC-16 did not have any prominent effect on the protozoal count, the bacterial count increased significantly in comparison to control group. Total nitrogen concentrations fell significantly while a significant increase was observed in the ammonia nitrogen content in the supplemented group at 6 hours after feeding. The animals of supplemented group showed a significant increase in body weights.